Nanoporous Crystalline Materials for the Recognition and Applications of Nucleic Acids - Yu, Long; Wang, Yuhao; Sun, Yuqing; Tang, Yongling; Xiao, Yuxiu; Wu, Gaosong; Peng, Shuang; Zhou, Xiang (Advanced materials (Weinheim), 2025)
Nucleic acid plays a crucial role in countless biological processes. Hence, there is great interest in its detection and analysis in various fields from chemistry, biology, to medicine. Nanoporous crystalline materials exhibit enormous potential as an effective platform for nucleic acid recognition and application. These materials have highly ordered and uniform pore structures, as well as adjustable surface chemistry and pore size, making them good carriers for nucleic acid extraction, detection, and delivery. In this review, the latest developments in nanoporous crystalline materials, including metal organic frameworks (MOFs), covalent organic frameworks (COFs), and supramolecular organic frameworks (SOFs) for nucleic acid recognition and applications are discussed. Different strategies for functionalizing these materials are explored to specifically identify nucleic acid targets. Their applications in selective separation and detection of nucleic acids are highlighted. They can also be used as DNA/RNA sensors, gene delivery agents, host DNAzymes, and in DNA‐based computing. Other applications include catalysis, data storage, and biomimetics. The development of novel nanoporous crystalline materials with enhanced biocompatibility has opened up new avenues in the fields of nucleic acid analysis and therapy, paving the way for the development of sensitive, selective, and cost‐effective diagnostic and therapeutic tools with widespread applications.